Pengaruh Kepemimpinan dan Pelatihan Terhadap Kinerja Melalui Komitmen Organisasi PT. Ujang Jaya International - Muzdalifah, Muzdalifah (Jurnal Informatika, 2024)
The purpose of this research is to determine and analyze the influence of leadership on performance, the influence of training on performance, the influence of leadership on organizational commitment, the influence of training on organizational commitment, the influence of organizational commitment on performance, the influence of leadership on performance through organizational commitment, the influence of training on organizational commitment. the influence of training on performance through organizational commitment. This research uses a type of causal research using a quantitative approach with a sample of 92 respondents who are employees of Ujang Jaya Internasional. The data collection technique uses interviews and a list of statements such as a questionnaire and the data analysis technique uses Partial Least Square (SmartPls) to test the seven hypotheses proposed in this research. The results of the research show that leadership has a significant effect on performance, training has a significant effect on performance, leadership has a significant effect on organizational commitment, training has a significant effect on organizational commitment, leadership has a significant effect on performance through organizational commitment (in other words, organizational commitment acts as a mediator), training has a significant effect on performance through organizational commitment (in other words, organizational commitment acts as a mediator).